A sociedade em conta de participação no direito de empresa do código civil de 2002 - Costa, José Maria da (2006)
Truogh the Law Nr. 10.406, of 10.01.2002, merged in our country a new Civil Code, to substitute the Beviláqua Code, effective since the second decade of last century (Law Nr. 3.071, of 01.01.1916). Besides deep modifications in the field of the civil law, the new Code unified, in same treatment, the civil and mercantile obligations, extinguished the distinction between civil and trade societies and created the entrepreneur societies. Immense difficulties, however, are set in delimiting the extension and effects of that junction between civil and commercial laws, mainly when is seen that, in the dawning of the new legislation, the civilists are self-neglecting the treatment of the enterprise law inserted in the Code, as if one just have added oil to water in same recipient, but such liquids continue not blending. However, having the mentioned junction of matters the authority of put right, a deeper reflection is necessary for the exegesis and application of the new legal system, so that there is not a commercialization of the civil law, or a civilization of the commercial right, both obviously improper. Just as an example, one can see that, on one side, the new Code gave to its devices a more open composition to make possible a more useful work of the judges. The commercial right, however, on its side, requests clear norms and firm rules. In a panorama as that, the application of principles as sociability and operationability in the field of the commercial right can generate insecurity, with social costs perhaps larger than the benefits that can be produced from the innovations. Even with the unified treatment, it is necessary to exist an peculiar hermeneutics of the commercial fact, different from that one that interprets the facts of civil nature, mainly when one treats the good-faith to be considered in the juridical businesses of mercantile nature, with its differences relative to the good-faith that governs the businesses among nonmerchants (CC, art. 113); it is necessary to consider in what extension must be applied, in the field of the commercial right, the principle of the freedom of negotiation, that is exercised within the limits of the social function of the contract (CC, art. 421); one must check how will incise, in the sphere of the commercial law, the new institute of lesion (CC, art. 157), that makes possible the annulment of a business by inexperience, above all in a field that the inexperience is part of the game. For that reflection of how the institutes and the societies of the ancient Commercial Code of 1850 come for the Civil Code of 2002, besides the own brought innovations, the most peculiar of all the societies was chosen - the participation bill - with its innovations and differences in relation to the previous ordering. An deductive feature analysis started from the historical notions of the trade and the evolution of the commercial law, went by the considerations on the Civil Code of 2002, stopped in the subject of the unification and in the principal aspects of interpretation of the new enterprise law, and analyzed how the societies were brought for the new ordering, and treated the society in participation bill, not with intention of exhausting the matter, but above all with the concern of enhancing the aspects of larger relief for the present time and of posting it as a center around which other discussions gravitates on generic aspects of larger relief. With those considerations, it is believed firmly that this study can contribute to stimulate and serve as a beginning of other works that attempt to place and to discuss, with the whole property, vastness and reflexes, the unification that took place in the obligation matter in the civilian and commercial fields, and of the own corporation law, starting from the specific analysis of that so agile, current, useful and sui generis society modality - the participation bill